THE COMPARISON OF SERUM CORTISOL LEVEL, CURB-65, AND PSI SCORES BEFORE AND AFTER TREATMENT IN COMMUNITY-ACQUIRED PNEUMONIA - Fatwa Sitta & Alwinsyah Abidin (International Journal of Research Science and Management, 2019)
Background: Pneumonia severity index (PSI) dan CURB-65 were deemed as themes established and commonly used scoring systems in community-acquired pneumonia (CAP). Serum cortisol concentration has been reported to be associated with severity of CAP. This study was aimed to compare the serum cortisol level, CURB-65, and PSI scores on hospital admission to day 7 of treatment in CAP. Methods: This was an observational analytic cohort study. The study was conducted at Haji Adam Malik Medan public hospital. Analysis were done using paired-t test if the data were normally distributed, and Wilcoxon test if otherwise. Results: There were significant differences values on initial and day 7 of cortisol levels (23.12±8.57 μg/dL vs 13.74±2.64 μg/dL; p < 0.001), CURB-65 scores (3.25±0.67 vs 1.47±0.67; p <0.001), and PSI scores (3.73±0.93 vs 2.2±0.76; p <0.001). Conclusion: There were significant differences of serum cortisol levels, CURB-65, and PSI scores on admission compared to day 7 treatment.